2020
DOI: 10.1186/s12913-020-05124-6
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ knowledge and practices regarding screening adult patients for adverse childhood experiences: a survey

Abstract: Background: Adverse Childhood Experiences (ACEs) are common and associated with many illnesses. Most physicians do not routinely screen for ACEs. We aimed to determine if screening is related to knowledge or medical specialty, and to assess perceived barriers. Methods: Physicians in Ontario, Canada completed an online survey in 2018-2019. Data were analyzed in 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Although it is estimated that 64% of American adults have reported at least one type of adverse childhood experience (ACE) in their lifetime (Felitti et al, 1998), screening adults for ACEs (or childhood adversity) is not currently a mandatory clinical assessment standard. Very limited data suggest that less than 30% of physicians (Maunder et al, 2020; Weinreb et al, 2010) and less than 33% of nurse practitioners (NPs; Branstetter et al, 2020; Kalmakis et al, 2017) routinely screen adults for ACEs in primary care. Traditionally, ACEs are defined as events that occur before 18 years of age, cause intense fear and/or suffering, may lead to lifelong physical or psychological symptoms, and require effective and ongoing communication between primary care clinicians and adult patients (Felitti et al, 1998; SAMHSA, 2014; Strauch et al, 2020).…”
mentioning
confidence: 99%
“…Although it is estimated that 64% of American adults have reported at least one type of adverse childhood experience (ACE) in their lifetime (Felitti et al, 1998), screening adults for ACEs (or childhood adversity) is not currently a mandatory clinical assessment standard. Very limited data suggest that less than 30% of physicians (Maunder et al, 2020; Weinreb et al, 2010) and less than 33% of nurse practitioners (NPs; Branstetter et al, 2020; Kalmakis et al, 2017) routinely screen adults for ACEs in primary care. Traditionally, ACEs are defined as events that occur before 18 years of age, cause intense fear and/or suffering, may lead to lifelong physical or psychological symptoms, and require effective and ongoing communication between primary care clinicians and adult patients (Felitti et al, 1998; SAMHSA, 2014; Strauch et al, 2020).…”
mentioning
confidence: 99%
“…Only two sites, SCPMG and Dartmouth CO-OP PBRN, tracked and reported the impact of screening on visit duration. Although time constraints were the mostcited anticipated barrier among providers completing the Becoming ACEs Aware in California training (71% of participants reported this concern), 1535,1552 Dartmouth CO-OP PBRN tracked and published data on visit duration, finding that visit length increased by less than 5 minutes for 91% of visits, 736 and SCPMG reported that ACE screening did not prolong visit length. These findings cohere with the literature, which has found little (usually adding under five minutes) or no increase in visit times.…”
Section: Screening Approaches and Toolsmentioning
confidence: 99%
“…Patients who present with significant toxic stress and nonneuropsychiatric conditions often receive care that does not adequately address the role that toxic stress physiology plays in their disease process(es). 1535,1536 Also, screening for ACEs in order to identify toxic stress…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With numbers of low-income, minority patients steadily increasing (HRSA, 2019a;Nath et al, 2016), FQHCs are well-positioned to enhance underserved patients' and communities' recovery and resilience by enacting systemwide trauma-informed care. Yet, to date, many FQHCs have failed to systematically inquire about patients' trauma exposure (Selwyn et al, 2019;Weinreb et al, 2010), with primary care physicians (PCPs) citing barriers such as limited time to counsel and provide psychoeducation to patients, lack of confidence in their ability to diagnose and treat PTSD, inadequate referral options, and patient financial burden (Chung et al, 2012;Maunder et al, 2020;Meredith et al, 2009). Without trauma screening, it is likely that PCPs remain unaware of a patient's trauma history and fail to incorporate aforementioned Event-and Experience-related factors into treatment plans as key therapeutic targets, despite their documented influence on outcomes.…”
Section: Gaps In the Literaturementioning
confidence: 99%